Respon rumput Odot (Pennisetum purpureum. CV. Mott) terhadap pemberian bokashi kotoran ayam pada tanah berpasir - Maria Erviana Kusuma (Fakultas Peternakan Universitas Kristen Palangka Raya, 2019)
The aim of this research is to know the effect of bokashi chicken manure on growth and production of Odot Grass (Pennisetum purpureum. Cv. Mott) on sandy soil and to know the dosage of bokashi chicken manure that giving the best result to growth and production of Odot Grass on sandy soil. This research was designed using Completely Randomized Design with single treatment of various doses of bokashi chicken manure (B) with 4 replications : b0 = 0 tons ha-1 bokashi chicken manure (control), b1 = 10 tons ha-1, b2 = 20 tons ha -1, b3 = 30 tons ha-1 and b4 = 40 tons ha-1. The results of this study showed that bokashi chicken manure gave effect to the number of tillers 8 week after planting and grass production. The dosage of 40 ton ha-1 bokashi chicken manure gave the best effect to number of tillers 8 week after planting and grass production. Keywords : Bokashi, chicken manure, Odot Grass.